In Situ Synchrotron Tomography of the Solidification of an Elektron 21 Mg Alloy. Issue 11 (16th August 2021) - Tolnai, Domonkos; Gavras, Sarkis; Wilde, Fabian; Hammel, Jörg U.; Bruns, Stefan
Abstract : The directional solidification of an Elektron 21 magnesium alloy is investigated by in situ synchrotron radiation tomography. To visualize the solidification process, samples of Elektron 21 are first heated to 800 °C, and the melt is held at this temperature for 5 min, to ensure temperature homogeneity. Subsequently, the samples are cooled with a cooling rate of 10 K min −1, while for every 35 s, one full tomogram is acquired. The evolution of the microstructure can be followed in 3D on the reconstructed tomograms. The contrast between rare‐earth metals and Mg enables to quantitatively analyze the changes in the morphology of the dendritic structure during solidification. At the onset of the detection, the growth of secondary dendrite arms occurs, which ends at the dendritic coherency point. From this temperature on, only the coarsening and coalescence of existing dendrite arms occurs. Abstract : The directional solidification of an Elektron 21 magnesium alloy is investigated by in situ synchrotron tomography. The samples are cooled from molten to solid state with a cooling rate of 10 K min −1 . At higher temperatures, the formation and growth of secondary dendrite arms occurs, whereas after the dendritic coherency point the coarsening and coalescence of these arms takes place.